2011
DOI: 10.1007/s00449-011-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of rapeseed straw by soaking in aqueous ammonia

Abstract: Pretreatment of lignocellulosic biomass has gained attention for production of biofuels. In this study, pretreatment by soaking in aqueous ammonia was adopted for pretreatment of biomass for ethanol production. A central composite design of response surface methodology was used for optimization of the pretreatment condition of rapeseed straw, with respect to catalyst concentration, pretreatment time, and pretreatment temperature. The most optimal condition for pretreatment of rapeseed straw by soaking in aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…In general, rapeseed straw is composed of three main fractions, including 34% cellulose, 19% hemicelluloses, and 6.9% lignin [12]. Relatively few studies have reported on the use of rapeseed straw as a bioenergy source [2,[9][10][11][12]. Thermal applications, such as pyrolysis, have been applied to energy production from rapeseed straw [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, rapeseed straw is composed of three main fractions, including 34% cellulose, 19% hemicelluloses, and 6.9% lignin [12]. Relatively few studies have reported on the use of rapeseed straw as a bioenergy source [2,[9][10][11][12]. Thermal applications, such as pyrolysis, have been applied to energy production from rapeseed straw [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high content of fermentable sugars (more than 60%), rapeseed straw has been suggested as a raw material for use as a biofuel feedstock [2]. In general, rapeseed straw is composed of three main fractions, including 34% cellulose, 19% hemicelluloses, and 6.9% lignin [12]. Relatively few studies have reported on the use of rapeseed straw as a bioenergy source [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pretreatment suffers from low glucose digestibility most likely linked to lower lignin removal compared to other alkali pretreatments [43]. Also, because xylan remains in solids, it blocks the access of enzymes to the substrate.…”
Section: Nhmentioning
confidence: 99%
“…Soaking in aqueous ammonia was adopted for corn stover and rapeseed straw for ethanol production at room temperature and 69 ˚C (Kim and Lee 2005;Kang et al 2012). Cañeque and Velasco (1998) focused on the application of ammoniated straw as animal feed, and they found that straw pretreated at 30% relative humidity and at a relatively high temperature increased the digestion rate and N content of the straw.…”
Section: Introductionmentioning
confidence: 99%